Blood year : the unraveling of Western counterterrorism - Kilcullen, David (Oxford University Press, 2016)
In Blood Year, David Kilcullen provides a wide-angle view of the current situation in the Middle East and analyzes how America and the West ended up in such dire circumstances. Focusing on the events of 2014--a year of massacres and beheadings, fallen cities and collapsing states--as a potential turning point in modern world history, this is an essential read for anyone interested in understanding not only why the region that the U.S. invaded a dozen years ago has collapsed into utter chaos, but also what it can do to alleviate the grim situation.